ANALISIS STATISTIK EFISIENSI ENERGI PENGGUNAAN TUNGKU SEKAM SEBAGAI BAHAN BAKAR ALTERNATIF RUMAH TANGGA - Christina, Yulia; Tsalsabila, Anissa; Ekawati, Deti Anggraeni; Amalia, Fanny; Septiani, Ratih Dwi; Novitri, Novitri; Gulo, Tetinia; Reza, Ahmad Khairul; Jayanti, Retno Dwi; Erfiani, Erfiani; Irzaman, Irzaman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Fuel usage in households commonly used in all levels of society. Has become a daily needs of households in the use of fuels, especially for cooking. Today, the limited supply of fuel gas causes the transition to alternative fuels such as rice husk furnace. Rice husk furnace is a medium that uses materials rice husk. Rice husk furnace produces an average value of efficiency reached 4.64% when the water used by 1 kg, 4,16% at 1,5 kg and 6,57% when water used weighin 2 kg. This efficiency value can be analyzed using a completely randomized design. This is because a completely randomized design is easier to analyze the data, especially research conducted in the laboratory. Keywords: Fuel, rice husk, rice husk furnace, efficiency, completely randomized design.